Biomechanical evaluation of an allograft fixation system for ACL reconstruction - Benca, Emir; van Knegsel, Kenneth P.; Zderic, Ivan; Caspar, Jan; Strassl, Andreas; Hirtler, Lena; Fuchssteiner, Christoph; Gueorguiev, Boyko; Windhager, Reinhard; Widhalm, Harald; Varga, Peter (Frontiers in Bioengineering and Biotechnology, 2022)
The purpose of the study was to compare the biomechanical stability, especially graft slippage of an allograft screw for tibial implant fixation in ACL reconstruction with a conventional interference screw. Twenty-four paired human proximal tibiae underwent ACL reconstruction, with the graft in one specimen of each pair fixed using the allograft screw and the other using the conventional interference screw. Specimens were subjected to cyclic tensile loading until failure. The two fixation methods did not show any statistical difference in load at graft slippage (p = 0.241) or estimated survival at slippage (p = 0.061). The ultimate load and the estimated mean survival until failure were higher in the interference screw (p = 0.04, and p = 0.018, respectively). Graft displacement at ultimate load reached values of up to 7.2 (interference screw) and 11.3 mm (allograft screw). The allograft screw for implant fixation in ACL reconstruction showed comparable behavior in terms of graft slippage compared to the interference screw but underperformed in terms of ultimate load. However, the ultimate load, occurring at progressive graft slippage, may not be considered a direct indicator of clinical failure.